2022
DOI: 10.3390/ijms23020876
|View full text |Cite
|
Sign up to set email alerts
|

New Light on an Old Story: Breaking Kasha’s Rule in Phosphorescence Mechanism of Organic Boron Compounds and Molecule Design

Abstract: In this work, the phosphorescence mechanism of (E)-3-(((4-nitrophenyl)imino)methyl)-2H-thiochroman-4-olate-BF2 compound (S-BF2) is investigated theoretically. The phosphorescence of S-BF2 has been reassigned to the second triplet state (T2) by the density matrix renormalization group (DMRG) method combined with the multi-configurational pair density functional theory (MCPDFT) to approach the limit of theoretical accuracy. The calculated radiative and non-radiative rate constants support the breakdown of Kasha’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…However, recent studies revealed that the presence of heavy atoms does not guarantee efficient ISC, while the nature of ligands may play a critical role in determining the radiation pathway [ 16 , 17 , 18 ]. To this end, the theoretical understanding of the relaxation processes is crucial, especially since conventional ISC between the S 1 and T 1 states is not necessarily the only pathway [ 19 , 20 ]. For instance, in a recently reported Au(III) complex, the S 1 state couples with T 4 and T 5 , resulting in phosphorescence as a major radiation pathway, while the relative Au(I) complex mainly demonstrates fluorescence due to the absence of triplet states energetically close to S 1 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies revealed that the presence of heavy atoms does not guarantee efficient ISC, while the nature of ligands may play a critical role in determining the radiation pathway [ 16 , 17 , 18 ]. To this end, the theoretical understanding of the relaxation processes is crucial, especially since conventional ISC between the S 1 and T 1 states is not necessarily the only pathway [ 19 , 20 ]. For instance, in a recently reported Au(III) complex, the S 1 state couples with T 4 and T 5 , resulting in phosphorescence as a major radiation pathway, while the relative Au(I) complex mainly demonstrates fluorescence due to the absence of triplet states energetically close to S 1 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%